Effectiveness Of Prenatal Yoga On The Level Of Anxiety And Long-Time Labor On Maternity Primiparous (Prodi DIII Kebidanan Blora Poltekkes Kemenkes Semarang, 2019)
The process of delivering on each mother must be different. Apparently, in addition to be the cause of the clinical, psychological atmosphere of the mother who does not support also contribute to complicate the process ofchildbirth. As a mother in a state of anxiety, excessive worry and fear, until eventually lead to stress. The purpose of the research was to determine the effectiveness of prenatal yoga on anxiety level and the second stage of labor longer on maternity primiparous. Methods research with quantitative approachquasi experimental with control grou pdesign. The total sample of 20 respondents, each group of 10 respondents. Bivariate analysis is done in two variables: the old stage II with categorical scale so usingtest. chi-square Jikasyaratchi-squareis not met using the Fisher exactprovided that if the value sig(p)0.05 then say no relationship signifikan.dan anxiety level has a categorical scale, if it does not qualifytest chi-square then used thealternative test Kolmogorov- Smirnov. The results of the study was prenatal yoga is proven effective against anxiety levels in maternal primipara withvalue significancy 0,003and prenatal yoga are effective against the second stage of labor longer on maternity primipara withvalue of significancy 0.003. Prenatal yoga is proven effective against anxiety levels in maternal and prenatal yoga primiparous effective against second stage of labor longer in primiparous birthmothers.